Review of the genus Phlugiolopsis Zeuner, 1940 (Orthoptera: Tettigoniidae: Meconematinae) from China - Bian, Xun; Shi, Fu-Ming; Chang, Yan-Lin (Zootaxa, 2012)
This paper reviews the genus Phlugiolopsis Zeuner, 1940, and describes 5 new species from China, Phlugiolopsis pectinissp. nov., Phlugiolopsis tribranchis sp. nov., Phlugiolopsis digitusis sp. nov., Phlugiolopsis trullis sp. nov. andPhlugiolopsis adentis sp. nov. A key to the species and distributional data in China are given. The type specimens are deposited in the Museum of Hebei University.